In situ gelling silk-elastinlike protein polymer for transarterial chemoembolization. (July 2015) - Poursaid, Azadeh; Price, Robert; Tiede, Andrea; Olson, Erik; Huo, Eugene; McGill, Lawrence; Ghandehari, Hamidreza; Cappello, Joseph
Abstract: Hepatocellular carcinoma annually affects over 700, 000 people worldwide and trends indicate increasing prevalence. Patients ineligible for surgery undergo loco-regional treatments such as transarterial chemoembolization (TACE) to selectively target tumoral blood supply. Using a microcatheter, chemotherapeutics are infused followed by an embolic agent, or the drug is encapsulated by the embolic moiety; simultaneously inducing stasis while delivering localized chemotherapy. Presently, several products are used, but no universally accepted system is promoted because very disparate limitations exist. The goal of this investigation was to design and develop in situ gelling recombinant silk-elastinlike protein polymers (SELPs) for TACE. Two SELP compositions, SELP-47K and SELP-815K, with varying lengths of silk and elastin blocks, were investigated to formulate a new embolic that was injectable through commercially available microcatheters. The goal was to develop a composition providing maximal permeation of tumor vasculature while exhibiting effective embolic activity. The SELPs evaluated remain soluble until reaching 37 °C, when irreversible transition ensues forming a solid hydrogel network. SELP-815K formulated at 12% w/w with shear processing demonstrated acceptable rheological properties and clear embolic capability under flow conditions in vitro . A rabbit model showed feasibility of embolization in vivo allowing selective occlusion of lobar hepatic arterial branches.